Are random biopsies still useful for the detection of neoplasia in patients with IBD undergoing surveillance colonoscopy with chromoendoscopy?. Issue 4 (23rd January 2017) - Moussata, Driffa; Allez, Matthieu; Cazals-Hatem, Dominique; Treton, Xavier; Laharie, David; Reimund, Jean-Marie; Bertheau, Philippe; Bourreille, Arnaud; Lavergne-Slove, Anne; Brixi, Hedia; Branche, Julien; Gornet, Jean-Marc; et al.
Abstract : Background: Colonoscopy with pan-chromoendoscopy (CE) is superior to standard colonoscopy in detecting neoplasia in patients with IBD. Performing random biopsies in unsuspicious mucosa after CE remains controversial. Methods: Consecutive patients with IBD who underwent surveillance colonoscopy using CE were prospectively included. The standardised procedure used CE, performed targeted biopsies or endoscopic resection on suspicious lesions and then quadrant random biopsies every 10 cm. A panel of five expert pathologists reviewed histological slides with dysplasia. Logistic regression model was used to evidence the factors associated with neoplasia in any or in random biopsies. Results: 1000 colonoscopes were performed in 1000 patients (495 UC, 505 Crohn's colitis). In 82 patients, neoplasia was detected from targeted biopsies or removed lesions, and among them dysplasia was detected also by random biopsies in 7 patients. Importantly, in 12 additional patients dysplasia was only detected by random biopsies. Overall, 140 neoplastic sites were found in 94 patients, 112 (80%) from targeted biopsies or removed lesions and 28 (20%) by random biopsies. The yield of neoplasia by random biopsies only was 0.2% per-biopsy (68/31 865), 1.2% per-colonoscopy (12/1000) but 12.8% per-patient with neoplasia (12/94). Dysplasia detected by random biopsies was associated with a personal history of neoplasia, a tubular appearing colon and the presence of primary sclerosing cholangitis (PSC). Conclusions: Despite their low yield, random biopsies should be performed in association with CE in patients with IBD with a personal history of neoplasia, concomitant PSC or a tubular colon during colonoscopy. Trial registration number: IRB 001508, Paris 7 University.